Towards a definition of male partner involvement in the prevention of mother-to-child transmission of HIV in Uganda: a pragmatic grounded theory approach - Patience A. Muwanguzi; Louise K. Nassuna; Joachim G. Voss; Joanita Kigozi; Alex Muganzi; Tom Denis Ngabirano; Nelson Sewankambo; Damalie Nakanjako (BMC, 2019)
Abstract Background Male partner involvement has been shown to increase mothers' uptake of Prevention of Mother-to-Child Transmission of HIV (PMTCT) and improve maternal and infant HIV treatment outcomes. Currently, male involvement in PMTCT is measured primarily through men's attendance at HIV testing and counselling which may not be a true reflection of their engagement. This study therefore set out to explore the meaning of male partner involvement and propose a definition and theoretical model of this concept in PMTCT in Uganda. Methods Eight focus group discussions and five in-depth interviews were conducted with couples at three public health facilities and community members in the health facility catchment areas in Uganda. The study employed a grounded theory approach underpinned by the pragmatic philosophical paradigm. Data were analyzed using the constant comparative method, performing three levels of open, axial, and selective coding. Results Of the 61 participants, 29 (48%) were male and the majority 39 (63.9%) were in long term marital relationships, while about half were self-employed 29 (47.5%). Three themes emerged for the meaning of male involvement in PMTCT (a) HIV treatment support (b) economic support and (c) psychosocial support. HIV treatment support included adherence support, couples' HIV counseling and testing, and clinic attendance during and after pregnancy. Participants expressed that men were engaged in PMTCT when they offered economic support by providing basic needs and finances or when they included their female partners in financial planning for the family. Psychosocial support arose from the female participants who defined male involvement as family support, perceived societal recognition and emotional support. Emotional support also included the absence of harm resulting from women's disclosure of HIV test results to their male partner. Conclusions This study proposes a new definition for male partner involvement in PMTCT in Uganda. The definition extends beyond men's clinic attendance and HIV testing and counselling. Further research should seek to develop and validate tools to accurately measure male partner involvement as the next step in the development of interventions to improve PMTCT outcomes.